Production–living–ecological space transition and its eco-environmental effects based on an improved area-weighted method: A case study of Gangcheng District, a typical industrial base in China - Wei, Yanan; Zhang, Yong; Chen, Longfei; Chen, Hongyan; Zhang, Xueqiang; Liu, Peng (Frontiers in Environmental Science, 2022)
In the context of rapid social and economic development, it is important to clarify the evolution process of production–living–ecological space (PLES) and its eco-environmental effects on the sustainable utilization of land resources on industrial bases. Based on existing research, it is difficult to accurately measure the differences in eco-environment quality caused by conversions between land-use types in different years. This paper puts forward an improved area-weighted calculation method of the eco-environmental quality index (EQI), combining the land-use transfer matrix and ecological contribution rate to analyze eco-environmental effects on typical industrial bases. The results show that PLES transitions in Gangcheng District from 2009 to 2020 have been mainly from agricultural production and grassland ecology to forest ecology space, from urban living to industrial production space, and from grassland ecology to agricultural production space. This improved method can capture the environmental changes caused by conversions between land-use types in different years. The EQI of agricultural production space increased from 0.373 to 0.388, while the EQI of forest ecology space decreased from 0.810 to 0.739, and the comprehensive EQI increased from 0.441 to 0.470, showing that the eco-environment quality of the study area was improved overall. The conversions of agricultural production and grassland ecology space to forest ecology space were the main factors in improving eco-environment quality, and the conversions of grassland and forest ecology to agricultural production and of agricultural production to industrial production space were the main reasons for the deterioration of eco-environment quality. This paper may contribute to the scientific planning of land-use direction, support the coordination of regional economic and ecological development, and provide case references for similar regions.